Validasi Instrumen Evaluasi Pembelajaran pada Mata Kuliah Biokimia Hasil Pertanian di Pendidikan Teknologi Pertanian, Universitas Negeri Makassar - Sukainah, Andi; Putra, Reski Praja; Fadilah, Ratnawaty; Mustarin, Amirah (Universitas Negeri Makassar, 2019)
Abstract. The purpose of this study is to produce a quality learning evaluation instrument with good validity and reliability so that it can be used continuously in the department Agricultural Technology Education (ATE), especially in the Biochemistry of Agricultural Product courses. Test data is obtained from instruments given to students. The instrument was in the form of several questions based on the material in the Semester Lecture Plan (SLP). Data were analyzed using IBM SPSS 20.0 software. This analysis is carried out to test the validity and reliability of the instruments used. Pearson correlation test results show there are only 10 questions that are valid from 15 questions available in the instrument. Cronbach's alpha instrument value, which is 0.701 with values between items in the range 0.638-0.714. Likewise, the reliability value of the instrument variant results is based on the C. Hoyt formula, which is 0.64. These results indicate, in addition to being valid, the ten instrument questions tested have good reliability, so that they are worthy of being applied as an evaluation instrument in the E-learning learning process.